(untitled) (Research, Society and Development, 2024)
Introduction: Liraglutide is a compound found in saxenda, an injectable drug, indicated for the treatment of overweight and obesity in adults. Objective: To describe the active mechanism of liraglutide to inform users about the correct use of the drug and its possible side effects. Method: Bibliographic review that used the PUBMED (National Library of Medicine) as a basis for the search for articles. Three descriptors were used in two associations: “liraglutide and obesity” and “(liraglutide obesity) AND (liraglutide effects)”. Results: The association “liraglutide and obesity” allowed the recovery of 45 manuscripts, of which 11 were selected to compose this review. For the association “(liraglutide obesity) AND (liraglutide effects)” 40 results were obtained, and 5 articles were selected. 16 articles were analyzed, and of these, 15 presented an effective result for weight loss. Among the side effects are: nausea, vomiting, diarrhea, constipation. Conclusion: It was observed that the use of liraglutide is relevant for reducing body weight, and that the increase in the amount of drug injected positively interferes with the cholesterol levels of people who use the drug.